PENGARUH KEPERCAYAAN MEREK, SWITCHING COST, DAN KEPUASAN KONSUMEN TERHADAP LOYALITAS KONSUMEN ( Studi pada pengguna ponsel Nokia pada mahasiswa FISIP Universitas Diponegoro angkatan 2010 sampai 2012 ) - Harum Amalun Nisa; Naili Farida; Reni Shinta Dewi (Universitas Diponegoro, 2013)
This study aims to determine the effect of brand trust, switching cost, and customer satisfaction on consumer loyalty in the mobile phone brand Nokia students FISIP UNDIP force 2010 to 2012. The sample amounted to 81 respondents with a sampling technique used is purposive sampling. Based on the test results indicate that the simultaneous F variable brand trust, switching cost, and customer satisfaction has positive and significant impact on customer loyalty at 50.6% which means that customer loyalty can be explained by brand trust, switching cost, and customer satisfaction of 50.6 %, and the remaining 49.4% can be explained by other variables. Partially based on t test variables in this study have positive and significant switching costs which have the greatest influence in the amount of 32.9%, while the lowest brand trust has the effect of 7.3%. the recomendations can be given in this study is a need to improve the quality in response to customer complaints handling. the need to improve the quality of the Symbian system hang if the order is not easy to use and less prone to viruses. Increasing improvements in network systems in order not to lag in accessing the internet.